Sosiologi Doa Pagi sebagai Praktik Lived Religion di SD Negeri Durensawit: (Studi tentang Ritual, Afeksi dan Budaya Sekolah) - Allya Farisha Azzahrani; Muh. Hanif (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study discusses the practice of morning prayer as a form of lived religion within the school culture of a public elementary school. Morning prayer is understood not only as a formal religious activity, but also as a daily ritual that shapes students’ emotional experiences, religious habits, and social interactions. This study aims to explain the empirical practice of morning prayer, the social relationships formed through it, and its implications for religious education and school culture. The research employs a qualitative approach using school ethnography methods. Data were collected through observations, interviews with the principal, Islamic Religious Education (PAI) teachers, classroom teachers, and students, as well as documentation of the school’s religious activities. The findings show that students participate in morning prayer routinely every day before lessons begin, followed by the collective recitation of short surahs from Juz 30. The daily practice of morning prayer gradually becomes a habit for students in starting their learning activities, both at school and at home. Teachers perceive morning prayer as an opening activity for learning, as well as a means of fostering emotional calmness, discipline, and students’ religious character. Students also reported feeling calmer, happier, and more prepared to learn after praying. In addition, the presence of Juz Amma books, Asmaul Husna texts, the school prayer room (mushola), and the habituation of congregational dhuha prayer indicate the institutionalization of a religious culture within the school, even though these practices are not yet fully included in the official schedule. The findings indicate that morning prayer has become part of students’ daily school experience. Through routine collective prayer activities, students gradually develop emotional readiness, discipline, and religious habits before learning begins.